Echos aus einem düsteren Reich - Herzog, Werner (Germany, 1990)
An Associated Press journalist Michael Goldsmith presents Jean-Bédel Bokassa, dictator of the Central African Republic from 1966 to 1979, through eyewitness testimony. Having followed Bokassa’s coronation ceremony for his newspaper, Goldsmith is treated as a spy and is taken prisoner due to an unfortunate circumstance. Returning to the places where he was imprisoned, Goldsmith also remembers the violent regime through the evocative sites of power he visits: the dictator’s villas, his zoo and his prisons. This violence is also brought to light through interviews: we hear the words of the dictator’s last wife, Augustine Assemat, his lovers, his numerous children, as well as David Dacko, President of the Central African Republic before and after Bokassa’s reign, and Bokassa’s lawyers. These images alternate with scenes from Bokassa’s trial (he was found guilty and sentenced to life in prison), along with photographs of people tortured and the farcical coronation ceremony in which he proclaimed himself emperor.
Duration: 01:33:00
Keywords: Documentary films